A Neurophysiological and Behavioral Assessment of Interventions Targeting Attention Bias and Sense of Control in Binge Drinking - Langbridge, Jessica E.; Jones, Richard D.; Canales, Juan J. (Frontiers in Human Neuroscience, 2019)
Attention bias modification (ABM) can decrease the selective visual attention paid to alcohol-related cues but has not been found to reliably reduce alcohol craving. Here, a cognitive intervention to decrease craving by increasing sense of control (Shamloo and Cox, 2014) was used as a complement. We investigated the effects of two such interventions administered singly or in combination. Participants were 41 binge drinkers (BDs) and 10 non-binge drinkers (NBDs). BDs received either ABM, sense of control training, both interventions, or no intervention, and were compared with NBDs who received no intervention. Groups were assessed on alcohol attention bias change including both reaction times and cue-elicited ERPs (visual dot-probe task), alcohol craving change, and alcohol consumption. BDs exhibited higher attention bias scores than NBDs. ABM had no effect on BDs’ behavioral or electrophysiological markers of attention bias. Sense of control training did not increase personal sense of control but protected against decreased task accuracy and against increased craving. BDs receiving the combined intervention consumed less alcohol in a bogus taste test than participants receiving no intervention. Taken together, the results suggest that ABM procedure may reduce alcohol consumption if combined with sense of control training.